Becoming an Active Subject: Women's Art Collective Eco-Artivism for Ecological Sustainability in Indonesia - Ambar Alimatur Rosyidah; Sahara Ulfa, Dhiya; Hermin Indah Wahyuni (Mudra Jurnal Seni Budaya, 2024)
This study explores the eco-artivism of women's art collectives for ecological sustainability by looking at actor-networks, eco-art as a non-human actor, and women's art collective negotiations. In Indonesia, eco-artivism is used to raise ecological awareness and strengthen socio-environmental protests in the ecological crisis. To explain the relationship of ecological sustainability in the artistic works of women's art collectives, we underline the connection between ecofeminism and Actor-Network Theory (ANT). We used a case study method with the Perempuan Pengkaji Seni (PPS) community, an art collective of female artists, workers, and researchers based in East Java, Indonesia. We find that the eco-artivism of women’s art collectives is an attempt to make women and nature become active subjects. These efforts can be seen in three resulting themes: the PPS network as a women's art collective, eco-art from the scars left by natural disasters to the impact of industrialization, and the negotiation of PPS as a women’s art collective for environmental sustainability.